Non-Target Activity Detection by Post-Radioembolization Yttrium-90 PET/CT: Image Assessment Technique and Case Examples - Kao, Yung Hsiang; Tan, Andrew EH; Lo, Richard HG; Tay, Kiang Hiong; Tan, Bien Soo; Chow, Pierce KH; Ng, David CE; Goh, Anthony SW (Frontiers in Oncology, 2014)
High-resolution yttrium-90 (90Y) imaging of post-radioembolization microsphere biodistribution may be achieved by conventional positron emission tomography with integrated computed tomography (PET/CT) scanners that have time-of-flight capability. However, reconstructed 90Y PET/CT images have high background noise, making non-target activity detection technically challenging. This educational article describes our image assessment technique for non-target activity detection by 90Y PET/CT which qualitatively overcomes the problem of background noise. We present selected case examples of non-target activity in untargeted liver, stomach, gallbladder, chest wall and kidney, supported by angiography and 90Y bremsstrahlung single photon emission computed tomography with integrated computed tomography (SPECT/CT) or technetium-99m macroaggregated albumin SPECT/CT.